Photobiocatalytic H2 evolution of GaN:ZnO and [FeFe]-hydrogenase recombinant Escherichia coli. Issue 12 (3rd June 2020) - Kosem, Nuttavut; Honda, Yuki; Watanabe, Motonori; Takagaki, Atsushi; Tehrani, Zahra Pourmand; Haydous, Fatima; Lippert, Thomas; Ishihara, Tatsumi
Abstract : The need for sustainable, renewable and low-cost approaches is a driving force behind the development of solar-to-H2 conversion technologies. Abstract : The need for sustainable, renewable and low-cost approaches is a driving force behind the development of solar-to-H2 conversion technologies. This study aims to develop a new strategy using a visible-light photocatalyst coupled to a biocatalyst for H2 production. Photocatalytic methyl viologen (MV 2+ ) reduction activity was investigated to discover active oxynitrides. In comparative studies with LaTiO2 N, BaTaO2 N and Ta3 N5, it was revealed that the suitable surface area, band gap and band edge potentials are some physical factors that are responsible for the photocatalytic behaviors of GaN:ZnO in MV 2+ reduction. The activity is enhanced at higher concentrations and the alkaline pH of triethanolamine (TEOA). The expression of an active [FeFe]-hydrogenase from Escherichia coli (Hyd + E. coli ) as a recombinant biocatalyst was confirmed by its MV˙ + -dependent H2 production activity. In the photobiocatalytic system of GaN:ZnO and Hyd + E. coli, the rate of H2 production reached the maximum level in the presence of MV 2+ as an electron mediator at neutral pH as a biocompatible condition. The present work reveals a novel hybrid system for H2 production using visible-light active GaN:ZnO coupled to Hyd + E. coli, which shows the feasibility of being developed for photobiocatalytic H2 evolution under solar light.